The Function of Confirmation Catechesis in Toraja Churches for Teenagers in the Era of ChatGPT - Leonardous Rano Masiku (MAHABBAH: Journal of Religion and Education, 2026)
ChatGPT is a technology that can generate text responses quickly based on human requests. This application is known through chatbots, where this technology has been widely used by teenagers to share stories, particularly about mental struggles, which can lead to loneliness if they are not guided properly. It is important to re-examine the meaning of confirmation catechesis of Toraja Church in educating teenagers so that they can develop mature characters based on Christian teachings, thereby becoming wiser in obtaining information such as from ChatGPT, which is based solely on internet data processing. Researchers used a descriptive qualitative approach to explore the function of confirmation catechesis at the Toraja Church, Karambe congregation during the period of ChatGPT's influence. Based on field research, researchers found that teenagers at Karambe Congregation only use chatbots to complete school assignments or catechisis tasks, so they have not yet reached the stage of providing information related to personal struggles. On the contrary, Confirmation Catechesis remain important for teenager in shape their character and knowing his faith in Christ personally, even though chatbots are a rich source of knowledge.